The Effectiveness of Using Canva as a Learning Media on the Vocabulary Mastery of Grade Seven Students of Public Tsanawiyah School 6 Solok - Vina Aryani; Hanomi Hanomi (Universitas Islam Negeri Imam bonjol Padang, 2023)
The research background in this study is that mastering vocabulary is very ‎important because vocabulary is one of the elements of the language that ‎must be mastered absolutely by those who learn Arabic. It is necessary to ‎have an educational media that is a means of Canva, which is expected with ‎this media in that students will be more interested and be more effective in ‎learning the Arabic language, especially on proficiency in vocabulary. Then, ‎the research objectives in this study are to find out the result of teaching ‎vocabulary among the seventh-grade students after using the Canva media, ‎and to know the effect of using the Canva media on mastering the vocabulary ‎of the seventh grade students in the Madrasah Tsanawiyah Hukumiyah ‎Islamiyah 6 Solok‏.‏‎ The researcher used the quantitative approach in the ‎experimental research method, with the type of research being Quasi ‎Eksperiment and Non-Equivalent Control Group Design, and the method of ‎collecting data is the test and its tools means questions in oral and written ‎form, and in analyzing the data with a T-test using the SPSS 26 program. ‎However, before the